The Effects of Phosphate Gangue on the Leaching of Uranium from Brannerite "Mining, Metallurgy & Exploration (2021)" - Rorie Gilligan; Aleksandar N. Nikoloski (Society for Mining, Metallurgy & Exploration, 2021)
Brannerite, UTi2O6, is the most common of the refractory uranium minerals and requires leaching under intense conditions to effectively extract the uranium contained within. Brannerite is often found together with apatite in metasomatic uranium deposits. Apatite and other phosphate gangue minerals can inhibit uranium leaching by generating phosphate ions which interfere with the reactions between acidic ferric sulphate and uranium minerals. As part of a detailed fundamental study on the leaching reaction mechanisms for brannerite, tests under a range of selected leach conditions were carried out with the addition of 10 g/L fluorapatite with the goal of identifying conditions where the negative effects of phosphate are reduced. Leaching was carried out for 5 hours with 0.05 mol/L Fe3+ as Fe2(SO4)3 with 0.25–1.00 mol/L H2SO4 and at temperatures between 25 and 96 °C. A single test was performed with 0.05 mol/L Fe3+ as FeCl3 and 1.00 mol/L HCl. In the sulphate system, the effect of phosphate was weakest at the highest acid concentration (1.00 mol/L H2SO4). In the chloride system, phosphate did not suppress uranium extraction, suggesting that HCl leaching could be a viable alternative for the leaching of high-phosphate refractory uranium ores.